Healthcare resource utilization and direct costs of transfusion-dependent thalassemia patients in Dubai, United Arab Emirates: a retrospective cost-of-illness study - Shaikha Alshamsi; Samer Hamidi; Hacer Ozgen Narci (BMC, 2022)
Abstract Background Patients with transfusion-dependent thalassemia (TDT) require lifelong blood transfusions and iron chelation therapy. Thus, patients afflicted with TDT often have to undergo blood transfusion and iron chelation therapy, which causes a major economic burden on them. However, this topic has not been reported in Dubai, United Arab Emirates (UAE). Hence, this study aimed to evaluate healthcare resource utilization and associated direct costs related to patients with TDT in Dubai, UAE. Methods For this study, a retrospective prevalence-based cost-of-illness analysis based on the UAE healthcare system and patient perspectives was conducted among patients with TDT treated at the Dubai Thalassemia Center in 2019. Information regarding healthcare resource utilization and direct medical costs was collected from the billing system connected to the electronic medical record system. Patients and their families were interviewed for direct non-medical cost estimations. Results A total of 255 patients with TDT were included in the study. The mean annual direct medical cost was estimated at AED 131,156 (USD 35,713) (95% CI: 124,735 - 137,578). The main driver of the medical cost for the participants as iron chelation therapy AED 78,372 (95% CI: 72,671 - 84,074) (59.8%), followed by blood transfusions, which accounted for AED 34,223 (95% CI: 32,854 - 35,593) 26.1% of the total direct medical costs. The mean annual direct non-medical costs was AED 2,223 (USD 605) (95% CI: 1,946 - 2,500). Age (p < 0.001), severe serum ferritin levels (p = 0.016), the presence of complications (p < 0.001), and the type of iron chelation therapy (p < 0.001) were significant predictors of higher direct medical costs incurred by the participants. Conclusion Transfusion-dependent thalassemia poses a substantial economic burden on the healthcare system, patients, and their families. Our results show that the highest medical cost proportion was due to iron chelation therapy. In this regard, efforts must be made to improve the patients' acceptance and satisfaction with their iron chelation therapy to increase their compliance and improve the effectiveness of treatment, which could play an essential role in controlling the economic burden of this disease. Moreover, greater support is essential for families that suffer catastrophic out-of-pocket expenses.